The influence of user participation attributes on e-government implementation success in developing countries: a study of Uganda - Kagoya, Sumaya M; Mbamba, Ulingeta O (University of Dar es Salaam Library Journal, 2021)
This paper examined the influence of user participation attributes on e-government implementation success in Uganda. The quantitative data were collected through a survey of 277 employees from three Ministries (ICT, Finance and Works) in Uganda and was analysed using PLS-SEM aided by Smart PLS3. Using Stakeholder theory as a primary theory for addressing user participation who are key stakeholders and UTAUT to capture the technology usage of e-government users. Findings revealed that user participation attributes have a significant positive influence on e-government implementation success in Ugandan context. Findings from the Smart PLS assessment measurement model portended that user participation attributes have a statistical positive relationship on e-government implementation success in Uganda. Therefore, policy makers, managers, Information System developers, electronic service providers, and e-government implementers should consider involving end-users in active e-government implementation process. This ensures accountability, transparency, trust in electronic-services and online-information from the central government to the users, among other benefits. These findings contribute to sparse literature of user participation in e-government implementation success in developing nations hence providing empirical foundation for future academia. More so, all stakeholders of e- government implementation work towards curbing the factors affecting and hindering end-users from active participation in e-government implementation in Uganda.